OPTIMALISASI RUTE DISTRIBUSI BBM PERTASHOP MENGGUNAKAN METODE SAVING MATRIX - Daffa Habibie Sumantry; Gilang Risyadhi, Yesta Sadha Syahputra, Paduloh (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Pertashop is a certain-sized outlet of Pertamina that has been prepared to meet the needs of consumers for non-subsidized fuel and LPG, as well as other Pertamina retail products. The main priority is given to locations in villages or cities that require Pertamina retail product services. The problem of fuel distribution from the Depot to Pertashop is that an optimal route has not been found yet. The purpose of this writing is to identify a more efficient route, using the saving matrix method. Then, the results will be further processed using the nearest insert method to achieve optimization. The result of the route analysis using the saving matrix and nearest insert methods found four routes that are targeted simultaneously with three trucks, each carrying 110 kiloliters of fuel. In conclusion, the analysis of the distribution route sequence using the Saving Matrix method has been carried out at Pertashop in Bekasi Regency with the route being, on the first truck delivery with a distance of 71.17 km, the second truck with a distance of 53.78 km, and the third truck with a distance of 38.54 km, this makes the route that will be distributed become optimal.